2022
DOI: 10.1007/s11682-022-00628-7
|View full text |Cite
|
Sign up to set email alerts
|

Hyperconnectivity between the posterior cingulate and middle frontal and temporal gyrus in depression: Based on functional connectivity meta-analyses

Abstract: BackgroundDisrupted whole-brain resting-state functional connectivity (RSFC) of the posterior cingulate (PCC) has been highlighted to associate with cognitive and affective dysfunction in major depressive disorder (MDD). However, prior ndings showed certain inconsistency about the RSFC of the PCC in MDD. This study aims to investigate the aberrant RSFC of the PCC in MDD using anisotropic effect-size version of seed-based d mapping (AES-SDM). MethodsWeb of Science and PubMed were searched for studies investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 82 publications
1
9
0
Order By: Relevance
“…Several previous studies have demonstrated structural as well as functional alterations in the left MFG in adolescents with MDD ( 13 , 46 48 ). The MFG is involved in regulating the default mode network activity via an antagonistic relationship, and in addition, it constitutes a core portion of the dorsolateral prefrontal cortex (DLPFC), which is the main hub of the central executive network responsible for executive and cognitive control such as response inhibition and working memory ( 49 ). By contrast, Wang et al ( 50 ) enrolled 30 adolescents with MDD and found that patients showed elevated fALFF in the left MFG relative to HCs at baseline, and that fALFF values increased further after electroconvulsive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated structural as well as functional alterations in the left MFG in adolescents with MDD ( 13 , 46 48 ). The MFG is involved in regulating the default mode network activity via an antagonistic relationship, and in addition, it constitutes a core portion of the dorsolateral prefrontal cortex (DLPFC), which is the main hub of the central executive network responsible for executive and cognitive control such as response inhibition and working memory ( 49 ). By contrast, Wang et al ( 50 ) enrolled 30 adolescents with MDD and found that patients showed elevated fALFF in the left MFG relative to HCs at baseline, and that fALFF values increased further after electroconvulsive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to healthy controls, melancholic patients also displayed decreased VMHC in the PCC ( 49 ). However, a recent meta-analysis MDD of the PCC showed higher FC in the bilateral MTG ( 47 ). The inconsistencies in these research results may have been caused by the different sample sizes, analysis methods, and software used, and the lack of a guarantee of complete homogeneity in the subjects selected.…”
Section: Discussionmentioning
confidence: 96%
“…The CG has been an important role subject of focus in previous pathological studies of depression, and the signs seen during the pathogenesis of depression are different between the anterior CG and posterior CG. The anterior CG is mainly related to self-control and emotional control, while the posterior CG is primarily related to early awakening, introspection, memory, and thought flexibility ( 47 ). Differences in the signs of depression between the two may be related to the core brain regions of the posterior CG involved in the default network.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al (2021) found significantly increased ALFF values in the left MFG in depression subjects. Zhu et al (2022) reported a negative association between the changed FC of the MFG and the severity of depression. Che et al (2020) reported that fALFF values of the left MFG were significantly increased in the peripartum depression group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased anterior cingulate-inferior frontal gyrus connectivity has been reported by Rolls et al (2019) . Zhu et al (2022) reported that the posterior cingulate showed higher resting-state functional connectivity with the right middle frontal gyrus (MFG) and the left middle temporal gyrus (MTG) in depressive patients. In addition, our correlation analysis showed that FC values were negatively correlated with patients’ SDS scores.…”
Section: Discussionmentioning
confidence: 99%